Comparison of Male and Female Agricultural Contributions in India (International Journal of Innovative Research in Engineering & Management, 2021)
Agriculture is perhaps the most inclusive word used to cover  various ways of providing food and other goods for the human  population of crops and domestic animals. Agriculture in  developing nations such as India prefers to utilize and attract  women, but is not considered as employees/employed. This  study focuses largely on the comparison of males and females  in agriculture, such as statistics and table data representing the  difference in the working of females and males for various  decades in agriculture. This article also provides complete data  about gender disparities in agriculture through resources (Labor  market, land, education, and technology). As just a  consequence of the globalization of commerce and agriculture,  and modifications in national policies, the scope and  possibilities of agro-based have considerably grown, resulting  in an expansion in business in this sector. India's fast-growing  rural market is delighting the globe, which is vital for the  corporate growth plan of the country.
Keywords: Agriculture; Gender; India; Men; Women